A comprehensive in-vitro/in-vivo screening toolbox for the elucidation of glucose homeostasis modulating properties of plant extracts (from roots) and its bioactives - Bauer, Ilka; Rimbach, Gerald; Cordeiro, Sönke; Bosy-Westphal, Anja; Weghuber, Julian; Ipharraguerre, Ignacio R.; Lüersen, Kai (Frontiers in Pharmacology, 2024)
Plant extracts are increasingly recognized for their potential in modulating (postprandial) blood glucose levels. In this context root extracts are of particular interest due to their high concentrations and often unique spectrum of plant bioactives. To identify new plant species with potential glucoselowering activity, simple and robust methodologies are often required. For this narrative review, literature was sourced from scientific databases (primarily PubMed) in the period from Jun 2022 to Jan 2024. The regulatory targets of glucose homeostasis that could be modulated by bioactive plant compounds were used as search terms, either alone or in combination with the keyword "root extract". As a result, we present a comprehensive methodological toolbox for studying the glucose homeostasis modulating properties of plant extracts and its constituents. The described assays encompass in-vitro investigations involving enzyme inhibition (α-amylase, α-glucosidase, dipeptidylpeptidase 4), assessment of sodium-dependent glucose transporter 1 activity, and evaluation of glucose transporter 4 translocation. Furthermore, we describe a patch-clamp technique to assess the impact of extracts on KATP channels. While validating in-vitro findings in living organisms is imperative, we introduce two screenable in-vivo models (the hen's egg test and Drosophila melanogaster). Given that evaluation of the bioactivity of plant extracts in rodents and humans represents the current gold standard, we include approaches addressing this aspect. In summary, this review offers a systematic guide for screening plant extracts regarding their influence on key regulatory elements of glucose homeostasis, culminating in the assessment of their potential efficacy in-vivo. Moreover, application of the presented toolbox might contribute to further close the knowledge gap on the precise mechanisms of action of plant-derived compounds.